2008
DOI: 10.1352/0895-8017(2008)113[178:mcfaft]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Multigroup Confirmatory Factor Analysis for the Adaptive Behavior Assessment System-II Parent Form, Ages 5–21

Abstract: The AAIDD has promulgated various models of adaptive behavior, including its 1992 model stressing 10 adaptive skills and its 2002 model that highlighted three conceptual domains. In previous studies on the Adaptive Behavior Assessment System-II (ABAS-II), researchers found support for a model including both 10 adaptive skills and three conceptual domains. To extend this review, we examined gender-invariant structure of adaptive behavior using the ABAS-II Parent Form, Ages 5-21, to answer four questions: Do the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 14 publications
3
8
0
Order By: Relevance
“…The Adaptive Behavior Assessment System (ABAS)-2nd Edition 14,36 (Hebrew and Arabic versions; http:// www.psychtech.co.il/New/Products/ABASII) generates a general adaptive composite (GAC) score that summarizes performance across all skill areas, except for work, and a subscore for each of the 3 general areas of adaptive behavior as follows. The conceptual composite score summarizes performance across the communication, functional academics, and self-direction skill areas.…”
Section: Adaptive Behavior Assessment System-2nd Editionmentioning
confidence: 99%
“…The Adaptive Behavior Assessment System (ABAS)-2nd Edition 14,36 (Hebrew and Arabic versions; http:// www.psychtech.co.il/New/Products/ABASII) generates a general adaptive composite (GAC) score that summarizes performance across all skill areas, except for work, and a subscore for each of the 3 general areas of adaptive behavior as follows. The conceptual composite score summarizes performance across the communication, functional academics, and self-direction skill areas.…”
Section: Adaptive Behavior Assessment System-2nd Editionmentioning
confidence: 99%
“…The adaptive behaviours of the ABAS-II are grouped into three subscales: the Conceptual Skills Composite, the Social Skills Composite, and the Practical Skills Composite, which together yield a general score referred to as the General Adaptive Composite (GAC). The ABAS-II has a high level of reliability and substantial evidence supporting its validity [22,23].…”
Section: Insert Table 4 About Herementioning
confidence: 99%
“…In prior research, a multigroup confirmatory factor analysis was performed on the factor loadings of the ABAS-II structure for males and females. Results of this study revealed the pattern of factor loadings are consistent across gender, and that the skill areas measure the same constructs for both male and female participants (Wei, Oakland, & Algina, 2008).…”
Section: Adaptive Behavior Assessment System-ii (Abas-ii; Harrison and mentioning
confidence: 60%